Lord of the wings eaudiobook - Andrews, Donna (Meg Langslow Mystery, 2015)
It's another holiday and Mayor Randall Shiffley has turned Caerphilly, Virginia, into Spooky City, USA. The residents are covering every window with cobwebs and roaming the streets in costume to entertain the tourists, and Meg's grandfather is opening a new 'Creatures of the Night' exhibit in the zoo. When a real body at the zoo and a suspicious fire at the Haunted House threaten to mar the town's creepy fun, it's up to Meg Langslow to save Halloween.